2014
DOI: 10.1002/ijc.29037
|View full text |Cite
|
Sign up to set email alerts
|

IgG1 anti‐epidermal growth factor receptor antibodies induce CD8‐dependent antitumor activity

Abstract: Anti-EGFR monoclonal antibodies (mAb) like Cetuximab are commonly used for treatment of EGFR 1 solid tumors mainly by exerting their therapeutic effect through inhibition of signal transduction. Additionally, IgG1 is a potent mediator of antibodydependent cytotoxicity (ADCC). In case of the IgG1, Cetuximab induction of ADCC in vivo is controversially discussed. In our study, we investigated the efficiency of Cetuximab-mediated ADCC in a humanized mouse tumor model in vivo and analyzed the contribution of immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…9 However, zalutumumab, as an IgG1 molecule, could induce both NK and myeloid effector cell-mediated ADCC, which shows the advantage of the IgG1 subclass in activating ADCC activity. 9 Moreover, Kubach et al 20 provide strong evidence of a novel mechanism of CD8 C T cell-mediated cytotoxicity induced by anti-EGFR mAb with an IgG1 isotype. Recently, Dillon et al 26 revealed that the heterogeneity of human IgG2 antibodies can affect structure and function, although additional studies are required to further characterize how this heterogeneity specifically affects panitumumab and its biological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 However, zalutumumab, as an IgG1 molecule, could induce both NK and myeloid effector cell-mediated ADCC, which shows the advantage of the IgG1 subclass in activating ADCC activity. 9 Moreover, Kubach et al 20 provide strong evidence of a novel mechanism of CD8 C T cell-mediated cytotoxicity induced by anti-EGFR mAb with an IgG1 isotype. Recently, Dillon et al 26 revealed that the heterogeneity of human IgG2 antibodies can affect structure and function, although additional studies are required to further characterize how this heterogeneity specifically affects panitumumab and its biological functions.…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies have suggested that the lack of ADCC activity could limit the efficacy of panitumumab in vivo mouse model. 19,20 The IgG2 isotype of panitumumab was chosen to minimize potential toxicity to EGFR-expressing normal tissues from ADCC and CDC. 15 Consequently, the construction of a novel ADCC-enhanced mAb by engineering panitumumab has not been reported, potentially due to concerns that improving the effector functions of panitumumab might increase the severity of additional side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a human HER2 transgenic mouse model, anti-HER2 monoclonal antibody treatment of murine D5 melanoma transfected with full-length human HER2 led to tumor regression and the development of immunological memory against the original tumor. 67,68 The effects of antibodies can be affected by the antibodies' subclass, glycosylation state, and affinity toward various tumor-derived antigens; [69][70][71] therefore, it remains unknown whether tumor-reactive antibodies generated in vivo possess similar functions to those used in monoclonal antibody therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In line with the above concept, there is evidence that the specific isotype and/or glycosylation status of an individual therapeutic mAb is relevant in this regard because these differences influence the aforementioned interactions . For example, the immunoglobulin G (IgG) isotype of EGFR‐specific mAbs is thought to be important in determining which lineage of cells predominates in mediating ADCC .…”
Section: Effects Of Targeted Therapies On Tumor Cells Relevant To Antmentioning
confidence: 94%